Characterization of the furin cleavage motif for HIV-1 trimeric envelope glycoprotein by intact LC-MS analysis. Issue 5 (14th January 2020) - Schneck, Nicole A.; Ivleva, Vera B.; Cai, Cindy X.; Cooper, Jonathan W.; Lei, Q. Paula
Abstract : We demonstrate a rapid deglycosylation strategy for recombinant HIV-1 envelope glycoprotein, enabling intact LC-MS mass measurement and furin cleavage monitoring. Abstract : Generating a soluble and native-like trimeric envelope glycoprotein (Env) with high efficacy as an immunogen has been a major focus for developing an effective vaccine against HIV-1. The Env immunogen is a heavily glycosylated protein composed of 3 identical surface gp120 and gp41 subunits that form into a trimer of heterodimers (3 × 28 N-glycan sites). During Env immunogen production, endogenous furin works to cleave a hexa-arginine motif connecting the gp120 and gp41 subunits, which is needed to ensure proper protein folding and a native-like conformation of Env. Verification of the overall identity and proteolytic cleavage of Env is therefore important for HIV-1 vaccine development and product quality. Herein, we report the first work using LC-MS to (1) achieve fast and accurate intact mass measurement of Env after deglycosylation and (2) confidently identify the furin cleavage sites.